Women – the recurring anomaly in the charcoal sector: Gender-responsive approaches for more inclusive, equitable and sustainable outcomes - Ihalainen, Markus; Awono, A.; Banda, E.; Moombe, K.B.; Mwaanga, B.; Schure, J.; Sola, P. (CIFOR-ICRAF, 2021)
This publication is part of a series of briefs describing findings from the EU-funded Governing Multifunctional Landscapes Sustainable Woodfuel project, which aims to contribute to knowledge, options, and networks for more sustainable woodfuel value chains across Sub-Saharan Africa.